Penurunan Keluhan Hot Flushes Perimenopause dengan Terapi Senam Aerobic Low Impact - Ahmaniyah Ahmaniyah; Emdat Suprayitno; Aulia Aulia; Arisda Candra Satriawati; Eva Nurhidayati (Fakultas Ilmu Kesehatan, 2022)
About two-thirds of elderly women experience symptoms of menopausal syndrome, which are physical and psychological symptoms complained of by perimenopausal and postmenopausal women, due to decreased ovarian function with fluctuations or decreased estrogen levels. One of the common symptoms often experienced is hot flashes, characterized by sudden feeling of heat and accompanied by flushing, sweating, chills and anxiety. So a solution is needed to deal with these symptoms, namely by doing light movements, namely low impact aerobic exercise. The purpose of this study was to determine whether there were differences in hot flushes before and after low impact exercise in perimenopause. This research method is pre-experimental with a one group pretest posttest design approach. Results: the mean before doing low impact aerobics is 13.43 and the mean after doing it is 22.2, which means that the greater the mean after doing low impact aerobics, the more hot flashes are seen in the respondents. From the statistical test, the P value <0.005 means that there are differences in symptoms of ho flashes between before and after doing low impact aerobic exercise in perimenopause. In conclusion, there is a decrease in complaints of hot flushes in perimenopause, namely before and after low impact aerobic exercise.